SIRT6 Relieves Acute Lung Injury by Enhancing PGC-1α Expression and Improving Mitochondrial Function - Li, Xiangyun; Mo, Yanshuai; Shi, Jia; Liu, Shasha; Bu, Shasha; Liu, Huayang; Li, Wenxing; Yu, Jianbo (Current Molecular Medicine, 2025)
<span class=
Keywords: mitochondrial dysfunction